The Left–Right Dimension, Europe and Voting in Bailout Europe - Heyne, Lea (2023)
This chapter investigates several questions concerning the relative importance of EU issue voting in Greece, Ireland, Portugal and Spain. First, the relationship between EU issue proximity and left–right proximity for voting behaviour. Second, the importance of both these issues contrasting mainstream and challenger parties. Third, whether EU parliamentary debates, measured in terms of tone, moderate the importance of EU issue voting. We use post-election online panel surveys collected in 2019–2020 in each of the bailout countries to analyse these questions. Our results show that, in all countries surveyed, EU issue voting does cross-cut the left–right dimension. Yet, left–right proximity has a higher impact on likelihood to vote for a party than EU issue proximity in all countries. Ireland stands out due to the relative irrelevance of both issues in explaining vote choice. European issue proximity to parties’ positions is a significant predictor of voting behaviour, but not a more important determinant of likelihood to vote than left–right for challenger parties. Finally, the tone employed by parties in EU parliamentary debates matters: For parties which have a more negative tone, EU proximity determines vote choice more strongly than for parties with a positive or neutral EU tone in parliament.